Appropriateness of Project-Based Learning- Students’ Perspective - Stoica, Ana Mihaela (Technium Social Sciences Journal, 2025)
This paper investigates students’ perceptions of Project-Based Learning (PBL) as a teaching approach and its implementation in classroom settings. As an active, student-centred teaching approach, PBL instruction emphasizes learner engagement, autonomy, and real-world application of knowledge. This method might be an appropriate option in today’s school background as it places the student and their interests in the centre and encourages them to actively participate in the learning process. The study examines how students experience and evaluate PBL in terms of motivation, participation, and the development of essential competences such as critical thinking, problem-solving, collaboration, and communication. We analyse in this article students’ perceptions of PBL usage in the classroom and the extent to which this teaching approach might be an appropriate solution to the challenges that students have to face due to the continuous technological, economic and societal changes, among other active learning approaches. The results provide insight into how PBL can enhance students’ motivation to learn and develop collaboration and competences which better prepare students for future academic and professional demands.